Quantification of the physical and physiological load of a boxing-specific simulation protocol - Thomson, E.; Lamb, K. (International Journal of Performance Analysis in Sport, 2017)
The aim of the study was to determine the physical and physiological responses to simulated amateur boxing of 3 × 3-min rounds. Using an externally valid technical and ambulatory demand, 28 amateur boxers (mean ± SD; age 22.4 ± 3.5 years, body mass 67.7 ± 10.1 kg, stature 171 ± 9 cm) completed the protocol following familiarisation. The physiological load was determined continuously via collection of mean (HRmean) and peak (HRpeak) heart rate, breath-by-breath oxygen uptake (O2), aerobic energy expenditure (EEaer), excess carbon dioxide production (CO2excess), ratings of perceived exertion (RPE) and post-performance blood lactate. Physical performance was quantified as the acceleration delivered to the target by punches. HRmean and HRpeak were found to exceed 165 and 178 b min-1, absolute O2 > 124.6 ml kg-1, EEaer > 30.7 kcal min-1 and acceleration via 78 punches >2697 g during each round. Mean blood lactate (4.6 mmol l-1) and CO2excess (438.7 ml min-1) were higher than typical resting values reflecting a notable anaerobic contribution. RPEs reinforced the intensity of exercise was strenuous (>6-8). For all measures, there were typical increases (p < 0.05; moderate ES) across rounds. Accordingly, boxers might consider high-intensity (>90% O2max) interval training in anticipation such exercise yields improvements in aerobic conditioning. Moreover, the current simulation protocol - the boxing conditioning and fitness test - could be used as a form of training per se and as a means to monitor intervention-based changes in aspects of boxing-related physiology and performance.